Effect of "diatomaceous earth" as a parasite in dairy cattle in the Piedemonte Llanero (Revista Sistemas de Producción Agroecológicos, 2011)
Parasitic diseases are a major concern in the livestock subsector in Colombia, The research institutions like ICA, CORPOICA, CEISA and CEGA among others have conducted and published various researches on damage to health standards and damages economic development. Moreover, animal production in the target is dominated by cattle ranching. "Almost 90% of the value of livestock production is for the livestock." Although in the foothills the trend is toward the dual purpose of the Department of Meta depart daily destined for the dairy industry in the Midwest, about 50 thousand liters of raw milk. In the constant search for new alternatives to get quality products without the presence of residues of drugs and / or chemicals in products of animal origin, two candidates for the degree in Agricultural Production, advised by a teacher Veterinarians and animal scientists from Eastern Plains University, planned and executed a research using female’s dairy cattle, to which it provides a natural product called “diatomaceous earth” to which benefits are attributed to control internal and external animal parasites. The product evaluation was conducted in the farm "El Rancho de San José"; is approximately two (2) hours from the Meta department’s capital, in the rural area of ​​El Castillo. There, were chosen at random thirty (30) dairy cows crossing Brown Swiss / Jersey, and some Holstein, to form three (3) experimental groups, each with ten (10) animals. At intervals of forty-five (45) days, data were collected in four (4) opportunities, the degree of infestation by external parasites, as well as samples for coprological and hematology. Additionally groups were sampled to determine the hysico- chemical quality of milk, in order to record possible changes in their characteristics over time’s work.
Keywords: parasites; hematology; cows